Growth Inhibition and Morphological Changes Caused by Lipophilic Acids in Mammalian Cells - Ginsburg, E. (1973)
Human (HeLa, Chang liver, L-132, and Intestine 407) and other mammalian (XC, SV3T3, and chick-embryo) cells in tissue culture are at least as sensitive to inhibition by lipophilic acids and nitrite as bacteria. Some of these compounds are the most frequently used antimicrobial food additives. Short-chain fatty acids (up to hexanoate) and parabens induce, at partially inhibitory concentrations, a jagged cell shape in continuous epithelial-like cell lines, such as HeLa, Chang liver, L-132, and Intestine 407. This morphological effect is not mediated or enhanced by butyryl cyclic AMP, which specifically affects fibroblasts.